2019
DOI: 10.1073/pnas.1810633116
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 is the central gatekeeper of intestinal mineral absorption essential for postnatal survival

Abstract: Zn2+, Mg2+, and Ca2+are essential minerals required for a plethora of metabolic processes and signaling pathways. Different categories of cation-selective channels and transporters are therefore required to tightly control the cellular levels of individual metals in a cell-specific manner. However, the mechanisms responsible for the organismal balance of these essential minerals are poorly understood. Herein, we identify a central and indispensable role of the channel-kinase TRPM7 for organismal mineral homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 58 publications
4
94
0
Order By: Relevance
“…Recently, a study discovered a critical role of a channel kinase, TRPM7 ("M" for melastatin), for mineral homeostasis. Mittermeier et al (2019) showed that TRPM7 depletion resulted in a sharply decline in calcium concentration, suggesting in addition to the factors discussed above, TRPM7 is also necessary for the massive calcium absorption at the intestine, representing another path that need more in-depth exploration. Therefore, the whole process is carefully controlled by 1,25(OH) 2 D via its properties of gene transcription regulation of the essential proteins including TRPVs, TRPM7, calbindin, PMCA1b, and NCX1 (Malloy et al, 1999;Fleet et al, 2002;Song et al, 2003).…”
Section: Calcium Metabolismmentioning
confidence: 99%
“…Recently, a study discovered a critical role of a channel kinase, TRPM7 ("M" for melastatin), for mineral homeostasis. Mittermeier et al (2019) showed that TRPM7 depletion resulted in a sharply decline in calcium concentration, suggesting in addition to the factors discussed above, TRPM7 is also necessary for the massive calcium absorption at the intestine, representing another path that need more in-depth exploration. Therefore, the whole process is carefully controlled by 1,25(OH) 2 D via its properties of gene transcription regulation of the essential proteins including TRPVs, TRPM7, calbindin, PMCA1b, and NCX1 (Malloy et al, 1999;Fleet et al, 2002;Song et al, 2003).…”
Section: Calcium Metabolismmentioning
confidence: 99%
“…Genetic association studies in humans revealed that point mutations in the TRPM7 gene cause a giant platelet disorder (macrothrombocytopenia) [ 60 ]. Experiments with mice currying a global or tissue-specific null mutation in the Trpm7 locus showed that TRPM7 is required for early embryonic development [ 22 , 61 , 62 , 63 , 64 ], thymopoiesis [ 61 ], morphogenesis of the kidney [ 63 ], cardiac rhythmicity and repolarization [ 65 ], systemic homeostasis of Zn 2+ , Mg 2+ and Ca 2+ [ 22 , 66 ], thrombopoiesis [ 60 ], and mast cell degranulation [ 67 ].…”
Section: Functional Characteristics and Physiological Roles Of Trpmentioning
confidence: 99%
“…Another study reported that the cleaved TRPM7 kinase can be detected in several cell lines and that the released kinase is able to translocate into the cell nucleus to phosphorylate histones [ 78 ]. The in vivo relevance of these reactions remains to be verified, because, unlike to the mouse strains with the Trpm7 null mutation, animals carrying the ‘kinase-dead’ point mutation were found to be fertile, and displayed normal pre- and postnatal development, if maintained under regular conditions [ 59 , 66 , 79 , 80 ].…”
Section: Functional Characteristics and Physiological Roles Of Trpmentioning
confidence: 99%
“…The C-terminal kinase region is cleaved under unknown stimuli, and the kinase phosphorylates nuclear histones. TRPM7 is responsible for oxidant-induced Zn 2+ release from intracellular vesicles [3] and contributes to intestinal mineral absorption essential for postnatal survival [532].…”
Section: Trpm2mentioning
confidence: 99%